The Challenge of Restoring Prudence to Accounting and Financial Reporting After Decades of Abandonment of Traditional Accounting Prudence - Hristina Oreshkova (International Business and Accounting Research Journal, 2023)
Over the past two to three decades, many large national and multinational companies operating in the European Union and elsewhere have experienced the effects of the profound regulatory changes in financial reporting, which are discussed in this study. Different, even conflicting, views have been expressed about the benefits of this process, which has affected fundamental accounting principles such as prudence. Academic research on prudence is extensive. Over the past decades, many academic studies have focused on prudence, which has been discussed in our previous work. A wide range of views and even conflicting arguments can be found in the literature.Â  This article focuses on views, considerations, and reflections from an academic and scientific perspective to support the thesis and critical analysis justifying the need to follow prudence in accounting and financial reporting. â€˜Prudenceâ€™ has been reintroduced in the 2018 Conceptual Framework for Financial Reporting (CF), which has always been considered the essential introduction to the International Accounting Standards (IAS) generally defining their philosophy. This article presents views, arguments, and findings based on long research prompted by the decision of the International Accounting Standards Board (IASB) to revise the CF in September 2010 and to remove â€˜prudenceâ€™ in favour of â€˜neutralityâ€™, which is considered to be a qualitative characteristic of the financial statement information. It is not the authorâ€™s intention to discuss the role of the CF or its objectives. The purpose of this study is to discuss the ongoing debate (despite the reintroduction of â€˜prudenceâ€ in the 2018 CF) on a complex and highly controversial issue that has been raised in the Discussion Paper (DP) and the Exposure Draft (ED), both of which contain proposals for a revised CF (January 2014, May 2015). The authorâ€™s thesis then, as now, is that for a considerable number of important reasons, it was imperative to restore the definition of â€˜prudenceâ€™ in the CF, to define its meaning as clearly as possible in order to avoid misinterpretation or misunderstanding, and to do so in a way that does not compromise or impair, but rather supports, â€˜neutralityâ€™. The CF has been under consideration by IASB members for a long time. It was expected in 2016 and even earlier, but was not issued by the IASB until March 2018. The terminology is mainly in the area of financial accounting and reporting under the Conceptual Framework, the International Accounting Standards (IAS), and the International Financial Reporting Standards (IFRS). The structure of the article is subordinated to the authorâ€™s objective to justify in an appropriate way that â€˜prudenceâ€™ should have been reintroduced in the CF as it has been achieved in 2018. The heuristic methods of knowledge used to achieve the authorâ€™s objective â€“ analysis and synthesis, induction and deduction, comparison, analogy, observation, descriptive method, etc. â€“ are generally accepted for scientific research in the field concerned and are often used because of their universal nature. A wide range of scientific literature, including foreign sources, has been reviewed and analyzed and the author has provided empirical evidence to support the thesis.